Psychological Problems Faced by Nautical Students of Politeknik Bumi Akpelni Semarang in Speaking Maritime English - Dewi, Filda Hulwani; Faridi, Abdurrachman; Saleh, Mursid (English Education Journal, 2021)
This study aimed to explain: (1) psychological problems faced by nautical students in speaking maritime English and it causes, (2) the effects of psychological problems to speaking maritime English, and (3) the class situation that expected by the students. This study employs a qualitative case study. In order to collect the data, the researchers used classroom observation, questionnaire, and semi-structured interview. This study revealed that: (1) There were only four of five prominents pychological problems faced by nautical students in speaking maritime English, they were; fear of mistakes because most of the students were afraid if they could not deliver the message clearly, mispronounced, and then being laughed by their friends; shyness because they felt that their friends had better ability rather than themselves; anxiety because they did not understand English well and some of them were lacking of vocabularies, grammar, and they were afraid of being negatively evaluated by their friends or lecturers; lack of confidence because they felt that their English were bad and other friends were better than themselves, so they did not believe in themselves and felt insecure. However, they did not have problems regarding their motivation because they really wanted to sail abroad. (2) There were effects of psychological problems because it made the students’ performance was not maximal yet. (3) Most of students wanted a relaxed, happy, and supportive speaking class situation, while some of them expected that speaking class was not too relaxed because they have to be forced in learning.